Knowledge, Attitudes and Behaviors of Medical School Students about HPV, HPV Vaccine and Cervical Cancer: A Survey Study in a Medical School - Ahmet Mert Ulucan; Şahsenem Beyzanur Şahinkaya; Hasan Ali Cırık; Hacer İlkay Genç; Ahmet Tarık Kozak; Amır Emamvırdı; Sefa Küçükkınalı; Mursel Duzova (Genel Tıp Dergisi)
Objective: This study aimed to determine the knowledge, attitudes and behaviors of students in a medical school about HPV, HPV vaccine and cervical cancer. Methods: The research was carried out in the students of Selcuk University Faculty of Medicine in April 2022. The universe of the study consisted of all medical school students and it was conducted with 125 volunteers who accepted the study. Participants were asked questions about HPV, HPV vaccine and cervical cancer. Results: One-hundred twenty five students participated in the study. The mean age was 20,89±2,339 (range 18-31). Of the 125 participants, 50,4% (n: 63) were female and 49,6% (n: 62) were male, and 74,4% (n: 93) were preclinical (1-2-3th year) students, and 25,6% (n = 32) were clinical (4-5-6th year) students. Majority of the respondents [ 86.4% (n=108)] reported that they did not have enough knowledge about HPV, HPV vaccine and diseases caused by HPV. Conclusion: As the result of the study, even medical school students were not fully informed about HPV, HPV vaccine, and cervical cancer. It is extremely important for more healty generation that medical students, who will be the pioneers of healthcare of the future and will educate the public on health and guide health policies, are given adequate training on HPV and HPV vaccine.